Nursing Students’ Perceptions of Learning Through a Service Learning Programme with Older Adults Living in Poverty in a High-Income Country: A Descriptive Qualitative Study. - Guerra-Marmolejo, Cristina; Morante-Garcia, Wladimir; Berthe-Kone, Ousmane; Chica-Pérez, Anabel; Dobarrio-Sanz, Iria; Granero‐Molina, José; Ortega-Ávila, Ana Belén (MDPI, 2024)
Background: Living in poverty negatively affects the biopsychosocial health of older adults. Nursing students need to develop competence to promote health and self-care behaviours amongst older adults living in poverty in high-income countries. Aim: To explore nursing students’ perceptions of a service learning programme aimed at promoting health and self-care among older adults living in poverty in a high-income country. Methods: A descriptive qualitative study was conducted with 37 nursing students recruited from a university in Southeastern Spain. Participants completed a service learning programme in which they conducted preventive home visits to older adults living in poverty. Data were collected through in-depth interviews and analysed using a reflexive thematic analysis. Results: Three key themes were developed: (1) service learning as a different way of learning, (2) as an active learning approach to bridge the theory–practice gap, and (3) to provide insight into an unknown side of nursing. Conclusions: By providing opportunities for active, experiential learning in real-world contexts, service learning was perceived by the nursing students as a methodology that helps to bridge the gap between theory and practice. Participating in a service learning programme with older adults living in poverty not only fosters emotional engagement, reflective practice, and the development of essential non-technical skills in nursing students, but it also prepares them to advocate for older adults living in poverty in a highincome country
Keywords: Aprendizaje servicio; Investigación activa en educación; Enfermería - Estudio y enseñanza superior; Service learning; Older adult; Poverty; Qualitative research; Nursing student